Spiritual and Welfare-Based Service and Service Guidance in Nagari Kumanis - Syaiful Marwan; Yose Rizal; Sarmen Aris; Ilhami Desrina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
By using a sustainable and participatory Participatory Action Research (PAR) approach, this community service aims to improve the social and spiritual welfare of the Nagari Kumanis community. One way to encourage community empowerment is by combining spiritual principles, local culture, and community participation in community service programs. Community service activities are carried out in three main forms: the customary Bakaua nagari and Randai cultural arts performances; monthly wirid nagari with speakers from UIN Mahmud Yunus Batusangkar; and coordination and evaluation of participation in village mentoring. The PAR methodology uses the stages of participatory planning, implementation, observation, and joint reflection. During the activity, traditional leaders, religious leaders, youth, village officials, and the community are the people who are being served. The results of the community service show that the customary Bakaua and Randai performances can increase social cohesion, cultural identity, and youth participation in preserving local values. Data collection was carried out through participant observation, in-depth interviews, and documentation of activities. The monthly wirid nagari helps people in the community understand and be aware of their spirituality, and it also makes social ties stronger. Meanwhile, participatory coordination and evaluation help the community create and assess the community's own community service program. Overall, this commitment shows that PAR-based mentoring that combines cultural and spiritual elements well can improve the welfare of the village community in a comprehensive and sustainable manner